Quantitative MRI detects delayed perfusion and impact of bronchial artery dilatation on pulmonary circulation in patients with cystic fibrosis - Leutz-Schmidt, Patricia; Grolig, Julian; Wucherpfennig, Lena; Sommerburg, Olaf; Eichinger, Monika; Wege, Sabine; Graeber, Simon Y.; Schenk, Jens-Peter; Alrajab, Abdulsattar; Kauczor, Hans-Ulrich; Stahl, Mirjam; Mall, Marcus A.; et al. (European radiology, 2025)
MRI detects abnormal lung perfusion in patients with cystic fibrosis (CF). However, little is known about the contribution of bronchial arteries to lung perfusion in CF. We hypothesized that delayed perfusion can be detected by dynamic contrast-enhanced (DCE-)MRI and that bronchial artery dilatation (BAD) is associated with changes in lung perfusion.
Gesehen am 09.02.2026